The Poem Thrax puer (Anthologia Latina 709) and the Humanism of Alfonso the Wise (Minerva, 2022)
Anthologia Latina 709 is an epigram attributed, among other classical authors, to Julius Cesar. It is collected in Alfonso the Wise’s Estoria de Espanna (History of Spain) as an example of the Roman politician’s literary skills. This paper aims to follow the remarkable development made by this text, whilst trying to decipher how it became known to Alfonso’s collaborators. The paper suggests several possibilities for this, whilst analysing the varied and possible ways of a complex transmission which helps us to appreciate the textual magnificence of Alfonso’s work.
Keywords: Estoria de Espanna; Alfonso the Wise; Anthologia Latina; Julius Caesar; Seneca; Paul the Deacon